Collision and displacement vulnerability to offshore wind energy infrastructure among marine birds of the Pacific Outer Continental Shelf. (1st December 2018) - Kelsey, Emma C.; Felis, Jonathan J.; Czapanskiy, Max; Pereksta, David M.; Adams, Josh
Abstract: Marine birds are vulnerable to collision with and displacement by offshore wind energy infrastructure (OWEI). Here we present the first assessment of marine bird vulnerability to potential OWEI in the California Current System portion of the U.S. Pacific Outer Continental Shelf (POCS). Using population size, demography, life history, flight heights, and avoidance behavior for 62 seabird and 19 marine water bird species that occur in the POCS, we present and apply equations to calculate Population Vulnerability, Collision Vulnerability, and Displacement Vulnerability to OWEI for each species. Species with greatest Population vulnerability included those listed as species of concern (e.g., Least Tern [ Sternula antillarum ], Marbled Murrelet [ Brachyramphus marmoratus ], Pink-footed Shearwater [ Puffinus creatopus ]) and resident year-round species with small population sizes (e.g., Ashy Storm-Petrel [ Oceanodroma homochroa ], Brandt's Cormorant [ Phalacrocorax penicillatus ], and Brown Pelican [ Pelecanus occidentalis ]). Species groups with the greatest Collision Vulnerability included jaegers/skuas, pelicans, terns and gulls that spend significant amounts of time flying at rotor sweep zone height and don't show macro-avoidance behavior (avoidance of entire OWEI area). Species groups with the greatest Displacement Vulnerability show high macro-avoidance behavior and low habitat flexibility and included loons, grebes, sea ducks, and alcids. Using at-sea survey data from the southern POCS, we combined species-specific vulnerabilities described above with at-sea species densities to assess vulnerabilities spatially. Spatial vulnerability densities were greatest in areas with high species densities (e.g., near-shore areas) and locations where species with high vulnerability were found in abundance. Our vulnerability assessment helps understand and minimize potential impacts of OWEI infrastructure on marine birds in the POCS and could inform management decisions. Graphical abstract: Highlights: We present a study of offshore wind energy infrastructure impacts on marine birds in the US Pacific Outer Continental Shelf. Using species-specific metrics, we calculated Population, Collision, and Displacement Vulnerability for 81 species. Species with highest Population Vulnerability included threatened species and year-round residents with small population sizes. Jaegers/skuas, pelicans, terns and gulls have high collision vulnerability. Loons, grebes, sea ducks, and alcids have high displacement vulnerability.